2008
DOI: 10.1111/j.1525-1594.2008.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Genotoxicity of Bovine Pericardium Preserved in Glycerol

Abstract: Bovine pericardium is a widely utilized biomaterial. Usually, after harvesting, it is advantageous that the pericardium be immersed in glycerol to improve its shelf life. This can induce some degree of toxicity in the material. The studies were performed in compliance with the rules of ISO 10993 and OECD 487, in the biological evaluation of medical devices. The material was prepared without previous washing. After sterilization by gamma radiation the pericardium was immersed in RPMI 1640 culture medium to fulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 2 publications
0
12
0
4
Order By: Relevance
“…Cytotoxicity test: Following the guidelines of ISD 10993-5 [14] , the cytotoxicity test was performed in culture microplates seeded with CHD cells and sample extracts diluted from 100 to 6.25% [15] . The microplates were incubated for 72 h at 37 °C in a humidified 5% CD 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Cytotoxicity test: Following the guidelines of ISD 10993-5 [14] , the cytotoxicity test was performed in culture microplates seeded with CHD cells and sample extracts diluted from 100 to 6.25% [15] . The microplates were incubated for 72 h at 37 °C in a humidified 5% CD 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Chinese hamster ovary cells (CHO-K1 lineage, ATCC number CCL-61) were maintained at 37°C in 5% CO 2 and 97% humidity in RPMI 1640 tissue culture medium (Gibco, USA), supplemented with 10% (v/v) fetal bovine serum (FBS -Gibco), (12). For subculturing and experiments, the cells were harvested using 0.05% (w/v) trypsin and 0.02% (w/v) ethylene diamine tetracetic acid (EDTA) in a saline phosphate-buffered solution, pH 7.4.…”
Section: Cell Line and Culture Conditionsmentioning
confidence: 99%
“…The differential response in accordance with the cell type was observed in several studies, Ridolfi et al observed a higher survival in 3T3 than for HaCaT depending of the solid lipid nanoparticles employed, while Benavides et al observed higher cytotoxicity in 3T3 than for HaCaT in the phototoxicity of a surfactant probably related to variation in the ability to deal with oxidative stress. Rodas et al also observed a dose‐dependent cytotoxicity of the glycerol used to preserve bovine pericardium.…”
Section: Resultsmentioning
confidence: 95%